Potret Kuota Perempuan di Parlemen - Ratnawati, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2004)
In response to the slow progress in improving women role in politics, an affirmative action has been adopted in Indonesia. A scheme, which popularly known as